Systems Biology Analysis of the Fate and Effects of Endocrine Disrupting Chemicals in Models of Adipose Tissue and the Gut Microbiota - Manteiga, Sara. (2017)
Abstract: A growing body of evidence links exposure to endocrine disrupting chemicals (EDCs) with obesity-related metabolic diseases. Adipose tissue (AT) plays a pivotal role in the development of obesity. AT actively regulates whole body energy homeostasis by orchestrating complex inter- and intra-cellular communications, effected via regulatory molecule networks. Sustained perturbation of metabolism by environmental factors such as over-nutrition can override homeostatic controls, leading to a cascade of signaling events that can result in inflammation, a hallmark of metabolic disease. In this work we investigated the fate and effects of a subset of EDCs in cellular models related to obesity, namely AT and the gut microbiota. Given their reported ability to interact with regulatory molecules in AT, we hypothesized that EDCs might act by perturbing metabolic and inflammatory signaling networks to elicit their effects. We explored this possibility by exposing adipocytes to low concentrations of EDCs. We employed a data-driven approach using metabolomics and proteomics methods to characterize cellular state and determine global patterns of alterations. Our findings showed that monoethylhexyl phthalate (MEHP) induces an inflammatory state, characterized by elevations in free fatty acids (FFA) and cytokines. We also observed broad dysregulation of lipid metabolism, suggesting involvement of the lipid metabolism regulator, peroxisome proliferator-activated receptor-γ (PPAR-γ) in the observed effects. Chemical inhibition of PPAR-γ abrogated the MEHP-induced cytokine expression, suggesting it is a mediator of the inflammatory effect. We then used model-driven 13C-labeling metabolic flux analysis to clarify the means by which MEHP elevated FFA levels. Flux simulations suggested this resulted from reduced ability to sequester FFA as triglycerides, though a clear understanding of the mechanism warrants future investigation. We also investigated the effects of EDCs on gut microbiota metabolism, which is intimately coupled to whole body energy metabolism in both health and disease. When we exposed isolated cecum cultures to EDCs we observed significant changes in 23% of the detected products of microbial metabolism, including lipids, neuroactive chemicals, and other signaling compounds. Dysregulation of microbiota metabolism could have negative outcomes on host health.; Thesis (Ph.D.)--Tufts University, 2016.; Submitted to the Dept. of Chemical and Biological Engineering.; Advisor: Kyongbum Lee.; Committee: Arul Jayaraman, Emmanuel Tzanakakis, Kurt Pennell, and Catherine Kuo.; Keywords: Systematic biology, Endocrinology, and Chemical engineering.